Peremptoary Challenges in Criminal Cases: A Comparison of Regulation in the United States, England, and Canada Notes and Comments - Heinz, Judith (Loyola of Los Angeles International and Comparative Law Journal, 1993)
Disclaimer: This summary was generated by AI based on the content of the source document.